The results of a comprehensive study of spring wheat accessions from the VIR collection according to their breeding characteristics - L. V. Volkova; O. S. Amunova; A. V. Kharina; E. V. Zuev (Труды по прикладной ботанике, генетике и селекции)
Background. The main strategy for the development of commercial cultivars with high yields and complex resistance to unfavorable factors is to attract new sources and donors of traits important for adaptability and agronomic use. Geographically distant cultivars as well as landraces may have unique sets of genes, so their potential requires studying under specific soil and climate conditions.Materials and methods. Twenty-four spring bread wheat accessions, included in the VIR collection in the period from 1928 to 2015, served as the material for the study. A scoring system for important breeding traits was used to characterize them. The following indicators were measured: the duration of the growing season and interphase periods, yield, lodging resistance, plant height, productive tillering, productivity of the main ear, weight of 1000 grains, protein content in grain, and chlorophyll content in leaves. Cultivars with a set of traits were identifying using the sum of points. Resistance to leaf and ear diseases common for Kirov Province was assessed.Results. Correlations between yield and traits important for breeding were observed, and the changes in correlation links depending on weather conditions were shown. Sources of valuable traits were identified. The effectiveness of the powdery mildew resistance genes Pm4b and Pm5, and Septoria resistance genes Stb2, Stb6 and Stb9 was not ascertained against local pathogen populations. The effectiveness of the Pm1 gene and several Lr-genes was observed. A positive trend of increasing the intensity index of cultivars (IIC) developed over a 90-year period was established.Conclusion. Source material for breeding new high-intensity immune cultivars in Kirov Province was selected for a set of valuable agronomic and biological characteristics.